Impact of Aneurysm Projection on Intraoperative Complications During Surgical Clipping of Ruptured Posterior Communicating Artery Aneurysms. Issue 3 (March 2016) - Fukuda, Hitoshi; Hayashi, Kosuke; Yoshino, Kumiko; Koyama, Takashi; Lo, Benjamin; Kurosaki, Yoshitaka; Yamagata, Sen
Abstract : BACKGROUND: Surgical clipping of ruptured posterior communicating artery (PCoA) aneurysms is a well-established procedure to date. However, preoperative factors associated with procedure-related risk require further elucidation. OBJECTIVE: To investigate the impact of the direction of aneurysm projection on the incidence of procedure-related complications during surgical clipping of ruptured PCoA aneurysms. METHODS: A total of 65 patients with ruptured PCoA aneurysms who underwent surgical clipping were retrospectively analyzed from a single-center, prospective, observational cohort database in this study. The aneurysms were categorized into lateral and posterior projection groups, depending on direction of the dome. Characteristics and operative findings of each projection group were identified. We also evaluated any correlation of aneurysm projection with the incidence of procedure-related complications. RESULTS: Patients with ruptured PCoA aneurysms with posterior projection more likely presented with good-admission-grade subarachnoid hemorrhage ( P = .01, χ 2 test) and were less to also have intracerebral hematoma ( P = .01). These aneurysms were found to be associated with higher incidence of intraoperative rupture ( P = .02), complex clipping with fenestrated clips ( P = .02), and dense adherence to PCoA or its perforators ( P = .04) by univariate analysis. Aneurysms with posterior projection were also correlated with procedure-related complications, including postoperative cerebral infarction or hematoma formation (odds ratio, 5.87; 95% confidence interval, 1.11-31.1; P = .04) by multivariable analysis. CONCLUSION: Ruptured PCoA aneurysms with posterior projection carried a higher risk of procedure-related complications of surgical clipping than those with lateral projection. ABBREVIATIONS: CI, confidence interval CTA, computed tomography angiography ICA, internal carotid artery mRS, modified Rankin Scale OR, odds ratio PCoA, posterior communicating artery SAH, posterior communicating artery WFNS, World Federation of Neurosurgical Societies